A Translational and Narratological Approach to Audio Describing Narrative Characters - Vercauteren, Gert (TTR, 2014)
The present article examines two issues in the field of audio description (AD) that so far have received little attention. Research in AD is highly multi- and interdisciplinary, and while semiotics, discourse analysis, narratology and film studies are some of the frameworks that are regularly used to study audio description, few attempts have been made to frame AD within the field of translation studies (TS). The first part of this article, therefore, describes a functionalist approach to audio description, both to strengthen the position of AD within TS and to contribute to a systematization of AD research. In the second part, such a systematic approach is applied to one question deemed “vital” in many national AD guidelines: the audio description of characters. Based on principles from formal narratology, a strategy is developed that allows describers to analyze characters in a structured, general way and to select relevant character information to be included in their descriptions.